Playing with the big boys : basketball, American imperialism, and subaltern discourse in the Philippines - Antolihao, Lou (University of Nebraska Press, 2015)
"'Playing with the Big Boys' traces the development of basketball in the Philippines from an educational tool during the early period of American colonial rule in the early twentieth century to a ubiquitous national pastime"--